A research and analytical study of the Shariah status and contemporary meaning of similarity: مشابہت کی شرعی حیثیت اور عصری معنویت کا تحقیقی و تجزیاتی مطالعہ - Saleem Ullah Masroor, Saleem Ullah Masroor; Dr. Muhammad Sarwar, Dr. Muhammad Sarwar (Al Khadim Research Journal of Islamic Culture and Civilization, 2026)
This research delves into the Shariah perspective on the concept of "similarity," exploring its current significance in the modern context. Through a combination of rigorous investigation and thoughtful analysis, the study aims to unravel the status of similarity within Islamic law. The objective is to bridge the gap between traditional interpretations and the challenges posed by contemporary issues. By presenting insights in clear and accessible language, this study endeavors to enhance understanding and contribute to discussions surrounding the dynamic interplay between Shariah principles and the evolving social landscape.